PEMANFAATAN MULSA ORGANIK Imperata cylindrica (L.), Mucuna bracteata DC. DAN KOMPOS PELEPAH KELAPA SAWIT (Elaeis guineensis Jacq.) TERHADAP PENGHAMBATAN PERKECAMBAHAN DAN PERTUMBUHAN GULMA Mikania micrantha H.B.K. - Siti Fatonah; Herman Herman; Sari Malinda; Mayta Novaliza Isda (DINAMIKA PERTANIAN, 2015)
The aim of this study was to determine effect of the thickness and type of organic mulch (Imperata cylindrica, Mucuna bracteata and compost of palm oil midrib) on germination and growth of Mikania micrantha weeds in polybag at garden. The experiment was designed in Randomized Block Design, with different treatment of three types of mulch, alone or in combination at 2.5 and 5 cm thickness, which contains 11 treatments. Each treatment was repeated seven replications. The results showed that mulch of I. cylindrica, M. bracteata, palm oil compost and their combinations inhibited the germination and growth of M. micrantha weeds. Almost all treatments mulch inhibited germination and growth of M. micrantha to decrease to 100 percent, except for M. bracteata mulch treatment with the reduction reached 97 percent.